(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
This article titled as “Kiprah Pasundan Istri (PASI) di Bandung on 1930-1970”. The main purpose in this research is to describe history Pasundan Istri organization background in 1930, to describe of development Pasundan Istri organization between 1930-1970 and to analyze the struggle effect of Pasundan Istri organization toward Women education between 1930-1970. To achieve research goals, the Historic Method used in this research consisting of heuristic, critical resources, interpretation and historiography, which of the sources obtained through study literature. In this regard, the study intended that the ideals and efforts of Pasundan Istri can be continued by Sundanese women in particular and Indonesian women in general. From the results, the researcher obtained data about the role of PASI which was established on April 30, 1930. This organization formed under the management of the Pasundan Association and founded by Mrs Emma Poeradiredja with 8 other women activists. Even though it is under the auspices of the Paguyuban Pasundan organization, PASI basically has a reglament and its own central committee named Centra Bestuur or Rengrengan Sesepoeh Pasoendan Isteri. At the beginning of its formation this organization was named Pasoendan Bagian Isteri (PBI), but in 1931 RSPI decided to change its name to Pasundan Istri (PASI) and selected Emma Poeradiredja as general chairman of PASI. PASI began the struggle initial steps by educating women and society in general by contributing to women’s empowerment in the form of a broad education. High sense of empathy and an effort to preserve regional cultural arts. This research is expected to be useful in learning history in schools, especially at the high school level and be a recommendation for other research on local history.